1977
DOI: 10.1530/jrf.0.0490101
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and follicular factors affecting maturation of sheep oocytes in vitro and their subsequent developmental capacity

Abstract: Oocytes removed from, or retained within, non-atretic and atretic follicles of different sizes were cultured for 24 h in the presence of a variety of hormones in an attempt to identify the factors affecting oocyte maturation in vitro. Resumption of meiosis was assessed morphologically; the developmental capacity of oocytes after culture was determined by transfer to the oviducts of inseminated ewes. About 70% of oocytes cultured after removal from follicles of different sizes resumed meiosis in vitro, but they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
142
1
4

Year Published

1983
1983
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(154 citation statements)
references
References 17 publications
7
142
1
4
Order By: Relevance
“…This would permit resumption of oocyte meiosis in a manner similar to normal maturation until the degenerative process affects the oocyte as well. That oocyte maturation during atresia is similar to normal maturation is suggested not only by the present findings on oocyte respiration, but also by the finding that maturing oocytes isolated from atretic follicles can be fertilized (sheep: Moor & Trounson, 1977;rat: R. H. Braw, unpublished).…”
Section: Discussionsupporting
confidence: 67%
“…This would permit resumption of oocyte meiosis in a manner similar to normal maturation until the degenerative process affects the oocyte as well. That oocyte maturation during atresia is similar to normal maturation is suggested not only by the present findings on oocyte respiration, but also by the finding that maturing oocytes isolated from atretic follicles can be fertilized (sheep: Moor & Trounson, 1977;rat: R. H. Braw, unpublished).…”
Section: Discussionsupporting
confidence: 67%
“…Un total de 4 615 ovocytes a été utilisé dans une série d'expériences destinées à évaluer l'effet respectif des différents composants du milieu de maturation in vitro (MIV) sur l'acquisition par les ovocytes bovins de leur compétence à se développer in vitro après fécondation (compétence cytoplasmique). Les (Moor and Trounson, 1977;Zhang and Armstrong, 1989); 2) the presence of serum in the IVM medium (Downs etal, 1986); and 3) the association of follicular or cumulus cells (ie somatic factors) with the maturing oocyte (Vanderhyden and Armstrong, 1989 (Staigmiller and Moor, 1984;Critser et al, 1986;Lu and Gordon, 1987;Lutterbach et al, 1987;Faundez et al, 1988;Chikamatsu et al, 1989 It has been shown that cumulus expansion is not necessary to achieve normal nuclear configurations during IVM (Sirard et al, 1988 (Jinno et al, 1989;Downs et al, 1991 ), rat (Shalgi et al, 1979;Vanderhyden and Armstrong, 1990), rabbit (Yoshimura et al, 1989), goat (Younis et al, 1991 sheep (Moor and Trounson, 1977;Staigmiller and Moor, 1984), and cow (Fukushima and Fukui, 1985;Brackett et al, 1989;Zuelke and Brackett, 1990). However, other authors have reported no effect of exogenous hormones (Fukui and Ono, 1989;Keefer et al, 1993).…”
unclassified
“…ln vitro matured cumulus enclosed bovine oocytes behave similarly (Thibault, G6rard andMdn6zo, 1975, 1976). Even when a male pronucleus develops after fertilization, regular cleavage seldom occurs (ovine, Moor and Trounson, 1977 ;bovine, Trounson et aL, 1977 ;.…”
mentioning
confidence: 99%